Russian Federation : 2017 Article IV Consultation-Press Release; Staff Report. (IMF Staff Country Reports; Country Report ;, 2017)
This 2017 Article IV Consultation highlights that the Russian economy stabilized in 2016, contracting by just 0.2 percent of GDP, after being hit in 2014 by the dual shocks of lower oil prices and sanctions. The more stable oil prices and improved financial conditions will support a return to growth in 2017, with an expected increase in real GDP of 1.4 percent. Growth is forecast to continue at 1.4 percent in 2018. With adverse demographics, and barring significant structural reforms that lifts productivity, potential growth is likely to stay at about 1.50 percent over the medium term. The main risk to the outlook remains a fall in oil prices.